Walter Benjamin liest Georg Simmel. Über Walter Benjamin und Georg Simmel von Marian Mičko - Barbisan, Léa (Simmel Studies, 2016)
Marian Mičko’s book Walter Benjamin und Georg Simmel (2010) gives a precise insight into Benjamin’s debt towards Simmel’s philosophical method and characterization of modern experience. Centered on the similarities between their “phenomenology of modernity”, Mičko’s analysis widely disregards the discrepancies between Simmel’s and Benjamin’s assessments of modern experience, culminating in Benjamin’s criticism of the bourgeois concept of individuality and his commitment to a Marxist approach.